Interfaith Families and the Law in Indonesia: Islamic Law, National Policy, and Human Rights after Supreme Court Circular Number 2 of 2023 - Ahmad Yusam Thobroni; Nasruddin Yusuf (Antmind Review: Journal of Sharia and Legal Ethics, 2025)
Interfaith marriage in Indonesia entered a new phase with the implementation of Supreme Court Circular No. 2 of 2023, which prohibits courts from granting petitions for the registration of interfaith marriages. This study examines the challenges of legal protection for interfaith families in North Sulawesi amid the contestation among sharia norms, national policy, and human rights. Using a socio legal approach, the research finds that the new policy reinforces the exclusivist character of sharia norms in family law practice while widening the gap of legal uncertainty for interfaith couples. Families in North Sulawesi face a dilemma between the formal demands of religious and state law and their need to live together and secure their basic rights. Many couples resort to informal or semi formal solutions, such as formal conversion, dual registration, or marrying abroad, which generate new legal risks particularly regarding the status of children and inheritance rights. Local wisdom in North Sulawesi, including tolerance, interfaith dialogue, and inclusive social practices, has proven to be an important asset for dampening potential conflict, but it is not strong enough to ensure long term legal certainty and protection. These findings underscore an urgent need for regulatory reform and harmonization between sharia, legal pluralism, and human rights principles so that the protection of interfaith families can be realized fairly and equally in Indonesia. .